2000
DOI: 10.1007/pl00011711
|View full text |Cite
|
Sign up to set email alerts
|

Surgically treated Cronkhite-Canada syndrome associated with gastric cancer

Abstract: Cronkhite-Canada syndrome is generally accepted to be a benign disorder, with 374 reported cases to the present. Worldwide, there have been 18 previously reported cases of Cronkhite-Canada syndrome associated with gastric cancer. In this report we describe a case of a 52-year-old man with the clinical features of Cronkhite-Canada syndrome combined with gastric cancer. Although the gastric tumor was located at the antrum of the stomach, we performed a total gastrectomy because of the edematous swelling and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 8 publications
0
33
0
1
Order By: Relevance
“…Some scholars reviewed the worldwide literature on CCS, and found an association between CCS and gastric cancer, at a rate of 5.1% (19/374 cases). Egawa et al (10) reported that a serrated adenoma was retrospectively found in 40% (10/25) of the polypoid lesions. Serrated adenomas appear as saw-toothed, elongated polyps with dilated crypts with nuclear atypia.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars reviewed the worldwide literature on CCS, and found an association between CCS and gastric cancer, at a rate of 5.1% (19/374 cases). Egawa et al (10) reported that a serrated adenoma was retrospectively found in 40% (10/25) of the polypoid lesions. Serrated adenomas appear as saw-toothed, elongated polyps with dilated crypts with nuclear atypia.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous treatment approaches, including aggressive nutritional support,14 100 101 antibiotics,8 42 histamine receptor antagonists,14 cromolyn sodium,14 immune suppression (corticosteroids, azathioprine and cyclosporine),13 20 102 103 and surgery89 104 105—often in different combinations—have had variable success 4 6 100 102 106. Apart from nutritional support, corticosteroids are currently recommended as the mainstay of medical treatment,26 with azathioprine used for its steroid-sparing effect 13.…”
Section: Therapy and Outcomementioning
confidence: 99%
“…Previously, gastrointestinal polyps of CCS were not considered to be a high risk for malignant disease. However, the number of cases of CCS complicated with gastrointestinal cancer has increased (4)(5)(6). We herein report a patient with CCS complicated with cholangiocarcinoma who was previously diagnosed with gastric cancer and colon cancer treated with surgery.…”
Section: Introductionmentioning
confidence: 98%